2016
DOI: 10.11648/j.ijber.20160501.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Financial Literacy on Individual Choices Among Financial Access Strands in Kenya

Abstract: This paper investigates effects of financial literacy on individual choices among formal financial services, informal financial services, and complete financial exclusion in Kenya. The study employed cross-sectional analysis using FinAccess national surveys 2009 and 2013 for 6,598 and 6,449 individuals, respectively. Multinomial probit regressions show that financial literacy is a strong predictor of individual demand for financial services. Financial literacy scores increases with increasing level of formalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…It has been found that financial illiteracy is prevalent to a great extent in this population (Fernandes, 2015;Ali et al, 2018;Jiyane and Zawada, 2013). The financial literacy is a crucial factor that strongly affects financial access (Shibia, 2012;Nyamboga et al, 2014;Egbo et al, 2020) and performance of MSMEs (Rachapaettayakom et al, 2020;Njoroge, 2013;Ibrahim, 2017;Munyuki and Jonah, 2021) In the recent years, the results of various research studies showed that poor financial literacy is one of the key reasons for the failure of small firms It is also one of the factors that hinder MSMEs to explore the different sources of finance Another significant finding of the paper is that there exists an inconsistency in the dimensions/parameters, undertaken by the various researchers, to assess the extent of financial literacy of entrepreneurs. Hence, it is recommended that standardized questionnaire with a clear cut demarcation between parameters/dimensions of basic and advanced financial literacy should be developed to measure the level of financial literacy amongst entrepreneurs across the globe and the same can be validated.…”
Section: Financial Literacymentioning
confidence: 96%
See 3 more Smart Citations
“…It has been found that financial illiteracy is prevalent to a great extent in this population (Fernandes, 2015;Ali et al, 2018;Jiyane and Zawada, 2013). The financial literacy is a crucial factor that strongly affects financial access (Shibia, 2012;Nyamboga et al, 2014;Egbo et al, 2020) and performance of MSMEs (Rachapaettayakom et al, 2020;Njoroge, 2013;Ibrahim, 2017;Munyuki and Jonah, 2021) In the recent years, the results of various research studies showed that poor financial literacy is one of the key reasons for the failure of small firms It is also one of the factors that hinder MSMEs to explore the different sources of finance Another significant finding of the paper is that there exists an inconsistency in the dimensions/parameters, undertaken by the various researchers, to assess the extent of financial literacy of entrepreneurs. Hence, it is recommended that standardized questionnaire with a clear cut demarcation between parameters/dimensions of basic and advanced financial literacy should be developed to measure the level of financial literacy amongst entrepreneurs across the globe and the same can be validated.…”
Section: Financial Literacymentioning
confidence: 96%
“…All firms require funds to meet their fixed and variable costs, but most of the small business owners lack requisite investments to launch (Chimucheka and Rungani, 2011;Nkundabanyanga et al, 2014). It also helps in savings mobilization, market exchanges and capital allocation (Shibia, 2012) of the firm. Finance is, therefore, considered essential for obtaining both tangible and intangible assets (Abiodun and Harry, 2016), and financial literacy plays a key role to procure the funds with ease.…”
Section: Financial Literacy and Financial Access Of Msmesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted in Kenya, Shibia and Kieyah (2016) found that financial literacy scores correspond with increasing levels of formality in the usage of financial products suggesting that the more financially literate people were, the more likely they would use formal financial services. Studies from the developed world, such as Mien and Thao (2015), Hogarth and Hilgert (2002), found that financial literacy was associated with responsible financial behaviors.…”
Section: Financial Literacy and The Use Of Formal Financial Servicesmentioning
confidence: 99%